2005
DOI: 10.19182/remvt.9945
|View full text |Cite
|
Sign up to set email alerts
|

Productivité numérique et pondérale des brebis produites du croisement entre la D’man et la race locale Queue fine de l’Ouest

Abstract: La productivité des brebis F1 issues du croisement entre la race prolifique D’man et la race locale Queue fine de l’Ouest (D’man x QFO) accouplées en croisement terminal avec des béliers de race Brune noire de Suisse (BNS) a été quantifiée et comparée à celle (i) des brebis QFO et D’man respectivement conduites en race pure en station de recherche à l’Ecole supérieure d’agriculture du Kef (Esak) et (ii) des brebis QFO conduites également en race pure mais en conditions de production (El-Mabrouka). A l’Esak, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Despite the difference among breeds (fat-tailed vs. thin-tailed), they drew similarly upon their reserves to give birth to lambs with the same birth weights (Bi-W) and similar growth parameters. However, in other studies, it has been reported that the breed significantly influenced the post-natal lambs’ growth in relationship with the own genotype effect, which manifests when lambs become independent of maternal effects [ 40 ]. The lambs’ birth weight was significantly lower in the second year ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the difference among breeds (fat-tailed vs. thin-tailed), they drew similarly upon their reserves to give birth to lambs with the same birth weights (Bi-W) and similar growth parameters. However, in other studies, it has been reported that the breed significantly influenced the post-natal lambs’ growth in relationship with the own genotype effect, which manifests when lambs become independent of maternal effects [ 40 ]. The lambs’ birth weight was significantly lower in the second year ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…However, at 30 and 70 days of age, males were heavier than females and the same tendency was recorded for both ADG. The lambs’ sex’s effect on the birth and advanced weights was previously reported, where male lambs were heavier than females [ 16 , 40 ]. The birth type significantly affected birth weight, weights at 30 and 70 days, and both ADG.…”
Section: Resultsmentioning
confidence: 99%